Determinants Of Turnover Intention With Organizational Commitment As Moderating - Vivi Alviyah; Saifudin Saifudin (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2022)
This study aims to determine the influence of self-efficacy, perceived organizational support, and Islamic work ethics on turnover intention with organizational commitment as moderation at PT. X Semarang. This research is quantitative research using primary data sources. The population in this study found 278 employees. The sampling technique used is purposive sampling, while the sample size is calculated using the Slovin formula so that the number of samples is 75 employees. This research uses multiple regression analysis with the moderated regression analysis (MRA) test. The results of this study are that self-efficacy (SE) positively and significantly affects turnover intention (TI). Perceived organizational support (POS) negatively and significantly affects TI. Islamic work ethic (IWE) negatively and significantly affects TI. Organizational commitment (OC) cannot moderate SE on TI. OC cannot moderate POS on TI. OC cannot moderate IWE on TI. This study provides a new perspective, namely from the employee’s point of view psychologically, the company can be used as a reference to reduce the turnover rate at PT. X Semarang. Specifically, regarding what factors need to be addressed so that the employee turnover rate can be reduced, this study can also reduce turnover rates by increasing perceived organizational support and the employee’s Islamic work ethic.